Analysis of IEEE 802.11e for QoS support in wireless LANs. - Mangold, S. (IEEE Wireless communications)
The IEEE 802.11e medium access control protocol is an emerging standard for wireless local area networks providing quality of service. An overview of this standard based on the current draft is presented on this article. We analyze the enhancements in 802.11 standard. The new hybrid coordination function of the IEEE 802.11e with its contention-based and contention-free (controlled) medium access control schemes is evaluated. The capability to provide QoS support is discussed by means of simulations.